Implementation OEE in Integrating Siemens S7-1200 Data with Odoo ERP - Muhammad Rafi Solakhudin; Muhammad Khoirul Hasin; Ii Munadhif (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2024)
The integration of perational Technology (OT) and Information Technology (IT) is crucial for enterprise-level decision-making regarding company effectiveness and productivity. This integration is achieved by developing an integrator system in the form of an API service, which facilitates the connection between Programmable Logic Controller (PLC) and Odoo Enterprise Resource Planning (ERP). Integration allows IT systems synergize with OT systems to processing data obtained from the performance of industrial machines. Analysis was conducted using the Overall Equipment Effectiveness (OEE) method to monitor the company’s production outcomes. A prototype sorting system with PLC for controlling was created as an OEE implementation. The API service acquires data from the plant and performs preliminary analysis in Odoo ERP. The analysis in Odoo ERP is conducted through the development of a manufacturing module that applies the OEE method calculations to monitor the effectiveness and efficiency of production procces. Once the calculation result is obtained, these data are monitored on Grafana in the form of pie charts and graphs. This research yielded insight into the design and implementation of an integration system for the bottle sorting process. The result also could be monitored in real-time using Odoo ERP and Grafana. Furthermore, the OEE analysis was matched with manual calculations in order to ensure its validity. Thus, this research enables the production process to be optimized and provides significant benefits to the company.